A sociolincuistic study of spanish language maintenance and lincuistic shift towards english among chicanos - Galindo, D Letticia (Lenguas Modernas, 2017)
Chicanos, as a lingual minority, comprise speech communities in urban ancl rural barrios: 'neighborhoods' throughout the Southwest. Such communities are dirversified and complex due to a range of varieties that exist along a Spanish-English continuum among its speakers. Because language choice is highly subjective, there exists a multiplicity of social and linguistic factors that promote or impede the use one variety over another given the context and interlocutors involved. This study adds to the data base of information by providing an overview of factors that surround language maintenance of Spanish and shift towards English among Chicano adolescents in two speech communities in Austin, Texas, along with a description of Spanish language varieties currently in existence and their designated functions and use.